CURRENT STATUS OF MYSID TAXONOMYIN SOUTHEAST ASIA - Sawamoto, Shozo (Marine Research in Indonesia, 2014)
This paper reviews the current status of mysid taxonomy in Southeast Asia, encompassing the South China Sea as far north as Hong Kong, the Andaman Sea, the Philippines, and the Indonesian seas as far south as the northern Australian waters. According to the 188 scientific papers published before 2013, 23 species in five genera of the Order Lophogastrida and 207 species in 63 genera of the Order Mysida have been recorded from these waters. This amounts to about 20 % of the recent species of these orders so far reported in the world. The occurrence recordsof these species were summarized in a table and a figure. On the basis of this body of information, it is suggested that there is an urgent need for research to improve our understanding of the biodiversity of mysids in this region.